Spatial Cluster Analysis by the Adleman-Lipton DNA Computing Model and Flexible Grids - Xiyu Liu; Laisheng Xiang; Xin Wang (Discrete Dynamics in Nature and Society)
Spatial cluster analysis is an important data-mining task. Typical techniques include CLARANS, density- and gravity-based clustering, and other algorithms based on traditional von Neumann’s computing architecture. The purpose of this paper is to propose a technique for spatial cluster analysis based on DNA computing and a grid technique. We will adopt the Adleman-Lipton model and then design a flexible grid algorithm. Examples are given to show the effect of the algorithm. The new clustering technique provides an alternative for traditional cluster analysis.